Meninjau Kebijakan Pekerjaan Penyandang Disabilitas di Instansi Pemerintah - Puspitasari, Citra; Laksmono, Bambang (Research and Development Agency Ministry of Home Affairs, 2021)
People with disabilities owned the same right to obtain employment to be civil servants. The government had created plenty of regulations to guarantee the right to obtain a job, starting from statutory regulations and various implementing regulations. However, a few problems in the scope of employment in government agencies still occur during this time, such as unachievable quotas, failure in procurement, and inequality for persons with disabilities. Moreover, it was not following the number of regulations that have been published. Hence, we were interested in analyzing the contents of the civil servant candidate recruitment policy and its implementation in 2017 through 2019 using a normative-empirical juridical approach, which was presented in a descriptive form. The Researchers examined statutory regulations and implementing regulations, supported by interview data from the stakeholders. In terms of content, the laws and regulations accommodated it quite well. Even though there were bad things, such as the Civil Servant Management regulation and technical regulations regarding the needs of employees in 2017 and 2018, that was considered discriminatory. Furthermore, Ministries and local governments have not fully followed the policies as written in the regulations. Briefly, there was an evolution of the regulations year by year; they were yet needed to improve policy content, although the policies continued to evolve for the better.